Highway «Western Europe — the Western China» as one of factors of development of infrastructure of transport system Republic of Kazakhstan. (Journal of Economic Research & Business Administration, 2015)
This article is devoted to problems of development of transport infrastructure of the Republic of Kazakhstan, in it the retrospective of development of transport branch is carried out, the important role of transport system as catalyst of social and economic development of Kazakhstan locates, arguments of are given that without improvement of available transport system successful integration of national economy into global world system of managing is impossible. The author especially focuses attention about increase of a role of industrial development of transport branch in connection with the forthcoming entry of the Republic of Kazakhstan into the WTO, adducing arguments of that the country has all prerequisites and opportunities to become the major interregional transit center. The author carried out the analysis of the main players carrying out a cargo transportation through the territory of Kazakhstan, the capacity and extent of the highways, available problems to the organizations of freght traffi cs. As a whole, the author summarizes that construction of the «Western Europe — the Western China» highway is economically effective project both on the region and at interstate level.
Keywords: Transport infrastructure; integration; interregional transit